FAKTOR-FAKTOR YANG MEMENGARUHI KESEDIAAN WANITA USIA SUBUR DALAM MELAKUKAN INSPEKSI VISUAL ASETAT (IVA) TEST DI WILAYAH KERJA PUSKESMAS CURUG - Runesi, Christin Wulan Mau; Nenohai, Genolvia Debryana; Ndun, Jesica Angeliq Grace; Ingrit, Belet Lydia; Tahapary, Prisca A (Nursing Current: Jurnal Keperawatan, 2025)
Cervical cancer is the second leading cause of death for women in Indonesia. One method of early detection is the Visual Inspection with Acetic Acid (VIA) test. This study aimed to identify factors influencing the willingness of women of childbearing age to undergo VIA testing in the working area of Curug Health Center, Tangerang Regency. The study population consisted of 34,290 women of childbearing age. An analytical cross-sectional design was employed, and 395 participants were selected using an accidental sampling technique. Data were analyzed using univariate analysis, bivariate analysis with the chi-square test, and multivariate analysis using multiple logistic regression. Education (p = 0.038), knowledge (p = 0.026), attitudes (p = 0.007), and husbands’ support (p < 0.001) were significantly associated with the willingness to undergo VIA testing. Husbands’ support emerged as the most dominant factor influencing willingness to participate in VIA screening. Education level, knowledge, attitudes, and husbands’ support were identified as key factors influencing women’s willingness to undergo VIA testing. Efforts to improve awareness and understanding of early cervical cancer detection among women of childbearing age in the Curug Health Center working area are essential to increase participation in VIA screening.